An exploration of service responses to domestic abuse among older people: findings from one region of the UK. Issue 4 (5th August 2014) - McGarry, Julie; Simpson, Christine; Hinsliff-Smith, Kathryn
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Domestic abuse continues to be largely hidden phenomenon. For older survivors this invisibility is further compounded by conceptual confusion surrounding domestic abuse and other forms of family violence. The purpose of this paper is to explore service responses to abuse among older people from across a range of sectors. Where possible the perspectives of older people themselves were explored. Design/methodology/approach – A mixed methods approach incorporating postal questionnaires and semi-structured telephone interviews. Agencies and organizations from both the statutory and voluntary sector who provided specific domestic abuse support services or general services and support for older people (aged 59 years and over) and older people, either as survivors of abuse or with an interest in the development of services for older people within one region of the UK were invited to take part in the project. In total, 18 individuals from a range of agencies and three older women survivors agreed to take part in the study. Findings – The findings highlighted three main themes, first, lack of conceptual clarity between domestic abuse and elder abuse, second, complexity of family dynamics and abusive relationships, and third, deficit in dedicated service provision for older survivors. The findings are discussed within the context of the existing literature and key recommendations include wider recognition of the significance of inter-professional education, training and working practices. Originality/value – This paper identifies the complexities and challenges that continue to face organizations in terms of recognition and provision of services for older survivors of abuse.